Report on currency and finance 1983- 84 - Reserve Bank of India (Bombay : Reserve Bank of India, 1983)
This is a report that contains the performance of the economy in 1983-84, with inclusion of the real national income recorded on estimated growth.
Issues also carry theme title.
hza 22/02/2019
Loans
Keywords: Currency question; Finance; Public Finance; Banks; Banking; Economic Conditions; India